Interactions between TiO2 nanoparticles and plant proteins: Role of hydrogen bonding. (March 2022) - Yuan, Biao; Jiang, Bing; Li, Han; Xu, Xiao; Li, Fei; McClements, David Julian; Cao, Chongjiang
Abstract: Titanium dioxide (TiO2 ) particles are widely employed in foods and supplements as lightening agents. A substantial fraction of the particles in commercial TiO2 ingredients fall within the nanoscale, i.e., they have diameters below 100 nm. A biocorona can form around TiO2 particles when they are incorporated into food matrices containing plant proteins. In this study, we investigated the molecular interactions between two hydrophobic plant proteins (gliadin and zein) and four types of surface-modified TiO2 nanoparticles (TCN, TCN-1, TCN-2 and TCN-3). Ultraviolet–visible absorption, fluorescence quenching, and Fourier transform infrared spectroscopy indicated that the plant proteins interacted with the surfaces of the TiO2 nanoparticles, resulting in changes in their molecular conformations. Quartz crystal microbalance analysis indicated that the mass of the hard corona increased as the number of hydroxyl groups on the surfaces of the TiO2 nanoparticles increased, which implied that hydrogen bonding played an important role in the formation of the biocorona. These results provide a better understanding of the interactions that may occur in food matrices containing both plant proteins and TiO2 nanoparticles. Graphical abstract: Image 1 Highlights: Plant proteins interact with TiO2 nanoparticles in food matrices to form biocoronas. These biocorona can be divided into 'hard' and 'soft' layers. Hydrogen bonds play an important role in biocorona formation. Protein adsorption/desorption depended on surface properties of the nanoparticles. Surface modifications affected the aggregation degree of the nanoparticles.